Revision of the Laonice bahusiensis complex (Annelida: Spionidae) with a description of three new species - Sikorski, Andrey V.; Radashevsky, Vasily I.; Castelli, Alberto; Pavlova, Lyudmila V.; Nygren, Arne; Malyar, Vasily V.; Borisova, Polina B.; Mikac, Barbara; Rousou, Maria; Martin, Daniel; Gil, João; Pacciardi, Lorenzo; et al. (Zootaxa, 2021)
The morphological reexamination of specimens previously identified as Laonice bahusiensis Söderström, 1920 from North European and Mediterranean collections, supported by the molecular analysis of freshly collected material, enabled the recognition of four different species in the region: the genuine L. bahusiensis, L. irinae n. sp. from North European waters, and L. grimaldii n. sp. and L. mediterranea n. sp. from the Mediterranean Sea. The morphology of these species is described and illustrated, and their distributions are clarified based on old and new materials. A key for their identification is also provided. The Bayesian analysis of the COI sequences (483 bp) showed that these four species form a clade, namely the L. bahusiensis species complex, morphologically characterized by the continuous dorsal crests on postbranchiate chaetigers in the adults. The genetic p-distances between the species of the complex ranged from 13.27% to 17.99%, while the intraspecific variability ranged from 0.6% to 1.57%. Together with the sister species Laonice cirrata (Sars, 1851), the L. bahusiensis complex formed the Laonice (Laonice) clade, which is morphologically characterized by the prostomium fused with the anterior peristomial margin. However, the monophyly of the L. bahusiensis complex, as well as that of the clade Laonice (Laonice), needs to be further supported through the analysis of a greater set of genes from a larger number of species.